Analisis Efektivitas Program Pembinaan Kewirausahaan dalam Meningkatkan Profitabilitas Usaha - Dewi, Ni Luh Putu Sandrya; Sujana, Ni Made Wanda Diajeng; Dewi, Luh Gede Kusuma (Jurnal Inovasi Akuntansi (JIA), 2024)
MSME come from various circles, one of which is students. Seeing the large number of students who are entrepreneurs, the Ministry of Education and Culture moved the government to hold an entrepreneurial student development program or called P2MW. The target of this program is students who have businesses nationally. The P2MW program is divided into several activities, namely workshops, talk shows, webinars/seminars, workshops, as well as coaching and funding related to entrepreneurship. One of the selected student businesses from Mahasaraswati University Denpasar is AW Dimsum. The aim of this research is to determine qualitatively the development of AW Dimsum's business profits before and after participating in the P2MW program. This research is qualitative in nature by emphasizing comparative descriptions of results before and after participating in the p2mw program and theoretical studies from several literatures. This research uses data collection techniques in the form of structured interviews and field observations. The results of this research show that the series of P2MW programs that have only been running for one month have already seen an increase in profits of around 10 – 15%. It is hoped that business owners will be able to be consistent in running their business and develop creative ideas for developing their business in the future.